(untitled) (The Macau Ricci Institute Journal, 2020)
write in support of making environmental responsibility central to the new economic paradigm. Others have spoken in support of this idea. I want to emphasize the role of private institutions, particularly higher education institutions, such as Silliman University, can play in demonstrating innovative leadership in this area. As important as it may be to promote political change, there’s no need to wait for a transformation in government policy priorities and the appropriate allocation of public resources. Private institutions, business corporations as well as NGOs such as educational institutions, can move ahead, in the expectation that their successful experiments will be replicated in public institutions and policies. Let me focus on those I know best, institutions of Christian higher education. Those that profess their Christian mission need to demonstrate and set good practices for winning the war against ecological destruction, rising poverty, and the health crisis, now made more visible and urgent by the Covid pandemic. Each college or university rooted in the tenets of Christian faith must be steadfast in its vision and mission in these changing times. But surely the teaching-learning contexts have changed. The ways of thinking about and carrying out the mission of Christian education must adapt strategies consistent with the current needs and challenges. In facing these challenges, Christian colleges and universities must re-examine their understanding of the faith and mission in the ministry of teaching. What are the moral imperatives? What is the nature and scope of our institutional response? How can we best respond in ways that move beyond the piecemeal approaches of the past?